2011 IEEE Trondheim PowerTech 2011
DOI: 10.1109/ptc.2011.6019459
|View full text |Cite
|
Sign up to set email alerts
|

Bad data detection at decomposition of state estimation problem

Abstract: Bad data detection is the most important problem in electric power system (EPS) state estimation. The paper addresses the algorithm of bad data detection by the test equation method at decomposition of state estimation problem. The decomposition algorithm includes structural and functional decomposition of the problem. The structural decomposition is carried out by dividing the calculated scheme into subsystems with respect to voltage levels. The functional decomposition is performed in accordance with the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…Small number of PMU installations makes it possible to obtain the calculated values of U, δ(using the so called "calculated" PMUs) at the other boundary nodes. The accuracy of the calculated values is comparable with the accuracy of measurements provided by real PMUs [23].…”
Section: A Distributed State Estimationsupporting
confidence: 71%
See 1 more Smart Citation
“…Small number of PMU installations makes it possible to obtain the calculated values of U, δ(using the so called "calculated" PMUs) at the other boundary nodes. The accuracy of the calculated values is comparable with the accuracy of measurements provided by real PMUs [23].…”
Section: A Distributed State Estimationsupporting
confidence: 71%
“…The State Estimation algorithm can be reduced to minimization of objective function with constraints in the form of a system of TEs. In this statement the SE problem can be solved directly in coordinates of the measured parameters [23].…”
Section: ) State Estimation For Each Subsystemmentioning
confidence: 99%
“… Improved efficiency of algorithms for Bad Data Detection [7] and better accuracy of SE results. The Dynamic State Estimation algorithms allow for:…”
Section: Resultsmentioning
confidence: 99%
“…, -resistance and reactance of line i-j. The studies (Kolosok et al, 2009) showed that the accuracy of measurements provided by the "calculated" PMU almost equals the accuracy of measurements received from the physical PMU; 3. As pseudo-measurements of power flows calculated on the basis of vector measurements from expressions:…”
Section: Application Of Pmu Measurements In Electric Power System Sta...mentioning
confidence: 97%